Electroreforming of polyethylene pretreated by thermocatalytic oxidation - Lee, Qian Ying (Nanyang Technological University, 2022)
Versatile properties of plastic have undoubtedly contributed to the global overreliance on it, which has led to expedited negative impacts on the environment and humans. Thus, this calls for immediate and decisive actions on the sustainable plastic chain. To this end, the current recycling methods generally suffered from low value recycled products, high energy consumption, unjustifiable costs in the recycling process, as well as the generation of other pollutants during the process. In this project, the use of thermochemical upcycling process to convert polyethylene (PE) into value added platform chemicals was discovered. The main products discovered were tartaric, oxalic, formic, acetic, and glycolic acid. The experimental findings have implications for contributing to a circular plastic economy and provide great opportunities to add the value of plastic waste after they have been recycled.